Adefovir dipivoxil sensitizes colon cancer cells to vemurafenib by disrupting the KCTD12-CDK1 interaction. (1st June 2019) - Yang, Jie; Xu, Wen Wen; Hong, Pan; Ye, Fei; Huang, Xiao-Hui; Hu, Hui-Fang; Zhang, Qi-Hua; Yan, Xin; Li, Bin; He, Qing-Yu
Abstract: Vemurafenib is a B-Raf V600E inhibitor that exerts significant inhibitory effects in melanoma but not in colon cancer, and the mechanism of vemurafenib resistance remains unclear. In this study, bioinformatics analysis of gene profiles in cancer cells treated with vemurafenib or its analog revealed that cell cycle progression is significantly affected by vemurafenib. We found that CDK1 is stably activated in the vemurafenib-resistant (VR) colon cancer sublines that we established, indicating that CDK1 activation is responsible for vemurafenib resistance. As the KCTD12-CDK1 interaction is necessary for CDK1 activation, we screened an FDA-approved drug library consisting of 616 compounds and identified that adefovir dipivoxil (AD), a nucleoside analog for treatment of HBV infections, disrupts the CDK1-KCTD12 interaction and induces G2 phase arrest in the cell cycle. Functional assays demonstrated that AD significantly inhibited colon cancer cell proliferation and tumorigenesis both in vitro and in vivo with no observed side effects. Furthermore, AD sensitized vemurafenib-resistant colon cancer cells and tumor xenografts to vemurafenib. This study reveals that CDK1 activation induces vemurafenib resistance and that AD is a promising therapeutic strategy for colon cancer both as a single agent and in combination with vemurafenib. Highlights: CDK1 activation induces vemurafenib resistance in colon cancer. Adefovir dipivoxil inactivates CDK1 by disrupting KCTD12-CDK1 interaction. Adefovir dipivoxil suppresses colon tumorigenesis by inducing cell cycle arrest. Adefovir dipivoxil sensitizes colon cancer cells to vemurafenib.